Generation of Celtic Key Patterns with Tree-based Collage Grammars - Klempien-Hinrichs, Renate; von Totth, Caroline (Electronic Communications of the EASST, 2010)
Tree-based collage grammars are a syntactic device for modelling visual languages. Celtic art provides such languages, which follow precise rules of construction, for instance key patterns and knotwork. In this paper, we study the syntactic generation of Celtic key patterns using tree-based collage grammars. Moreover, the regulation mechanisms we employ to ensure that only consistent key patterns are generated are compared with the mechanisms used in a previous study for knotwork.